Clinical characteristics of children and young people hospitalised with covid-19 in the United Kingdom: prospective multicentre observational cohort study - Swann,OV; Holden,K; Turtle,L; Pollock,L; Fairfield,CJ; Drake,TM; Seth,S; Egan,C; Hardwick,HE; Halpin,S; Girvan,M; Donohue,C; et al. (2020)
Abstract Objective To characterise the clinical features of children and young people admitted to hospital with laboratory-confirmed severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection in the UK, and explore factors associated with admission to critical care, mortality, and development of multisystem inflammatory syndrome in children and adolescents temporarily related to covid-19 (MIS-C). Design Prospective observational cohort study with rapid data gathering and near real time analysis. Setting 260 acute care hospitals in England, Wales, and Scotland between 17th January and 5 th June 2020, with a minimal follow-up time of two weeks (to 19 th June 2020). Participants 451 children and young people aged less than 19 years admitted to 116 hospitals and enrolled into the International Severe Acute Respiratory and emergency Infections Consortium (ISARIC) WHO Clinical Characterisation Protocol UK study with laboratory-confirmed SARS-CoV-2. Main Outcome Measures Admission to cr